E-MATCHING GAME IN TEACHING ENGLISH FOR YOUNG LEARNERS - Temaja, I (PEOPLE: International Journal of Social Sciences, 2017)
This study aimed at developing an educational game in Teaching English for Young Learners (TEYL). Young learners easily feel bored if they are taught by using conventional teaching method, therefore the teachers have to be creative in designing the teaching process. One of the ways can be done by teachers in order to make their teaching become fun is by providing a good media. One of media is in the form of a game. Teaching English through game is appropriate and needed, especially for teaching young learners. In addition, young learners love to learn through game. Therefore, this article aims at explaining how to create e-matching game and how to use it in teaching English. This game should be based on young learners’ characteristics. Specifically, this article discusses about: (1) the role of game in TEYL; (2) how to design and develop e-matching game; (3) how to teach young learners using e-matching game; and (4) the benefits of TEYL using e-matching game. This article is expected to give information for English teachers who want to develop e-matching game.